A Federal Resource Allocation and Social Sector Development: Evidence from Nigeria - Amakihe, Barthlomeu; Sadeeq, ’Wale (African Journal of Stability and Development (AJSD), 2018)
Nigeria has a revenue allocation scheme which ensures that national wealth is shared among the three tiers of government. This fiscal relationship is expected to ensure national development and improve the quality of life of the citizenry. Thus, federal resource allocation is, among other things, expected to be channelled towards the development of the critical sectors, particularly the social sector for the overall wellbeing and welfare of the citizenry. Using a blend of secondary and primary data, this paper assesses the link between federal resource allocation and its implications on social sector development in Nigeria. The paper found that the utilisation of federal allocation has not enhanced the development of the social sector in Nigeria and that there was low commitment to the development of the social sector at all levels, reflecting in poor budgetary allocation and weak policy framework. Specifically, we recommend an enhanced federal resource allocation to the social sector in line with international benchmarks, increased political commitment, consistent policy framework and effective anti-graft measures.